Contextualising shoreline protection by seagrass using lessons from submerged breakwaters. (5th October 2022) - Twomey, Alice J.; Callaghan, David P.; O'Brien, Katherine R.; Saunders, Megan I.
Abstract: Coastal ecosystems, such as seagrass meadows, have been heralded as a nature-based solution for coastal protection. However, the functions of seagrass meadows, including wave attenuation and sediment stabilisation, have typically been measured offshore and do not directly translate to coastal protection at the shoreline. In contrast, the protective effects of conventional submerged structures, such as breakwaters and artificial reefs, on adjacent shorelines have been well described and are predictable. Importantly, these artificial structures often cause erosion in adjacent areas. This study examines how seagrass may affect shoreline morphodynamics by making inferences from existing knowledge of conventional submerged structures. Both conventional submerged structures and seagrass meadows affect wave height and direction, yet this effect on longshore sediment transport has only been considered within the context of coastal defence structures. From the conventional literature on submerged structures, it is known that a constant rate of longshore sediment transport will result in a constant shoreline shape. Therefore, a change in the rate of longshore sediment transport, or gradient, generates changes in the shoreline shape and, hence, the shoreline morphodynamics. We propose that seagrass also has spatially heterogeneous effects on shoreline morphodynamics, with protection occurring in some locations and downstream erosion likely in others. Empirical and modeling research is required to test this hypothesis. In the meantime, this review suggests contexts under which seagrass may affect shoreline morphodynamics and provide shoreline protection. This research bridges the gaps in knowledge across marine ecology, physical oceanography and coastal engineering to overcome some of the challenges of interdisciplinary coastal science. Highlights: Breakwater literature is applicable to seagrass to predict coastal defence. Seagrass has a spatially heterogeneous effect on shoreline morphodynamics. Seagrass needs to generate a gradient in sediment transport to affect the shoreline. Seagrass can cause downdrift erosion.